Eyewitness recall and suggestibility in individuals with Down syndrome. Issue 12 (6th July 2016) - Collins, D.; Henry, L.
Abstract: Background: Many criminal justice professionals perceive the eyewitness skills of individuals with intellectual disabilities to be weaker than those of typically developing (TD) individuals. Down syndrome (DS) is one of the most common genetic causes of intellectual disabilities, yet there is no research addressing eyewitness skills in this population. This study examined the eyewitness recall and suggestibility of young people with DS. Method: Young people with DS and mental age‐matched TD children viewed a video of a non‐violent petty crime and were subsequently asked to freely recall the event before being asked general and specific questions incorporating both misleading and non‐leading prompts. Results: Compared with mental age‐matched TD individuals, young people with DS produced as much information, were just as accurate and were no more suggestible. Conclusions: The eyewitness memory skills of young people with DS are comparable to those of mental age‐matched TD children. The implications of these findings for the forensic context and eyewitness memory are discussed.